Modulating pH through lysine integrated dental adhesives. Issue 11 (November 2018) - Song, Linyong; Ge, Xueping; Ye, Qiang; Boone, Kyle; Xie, Sheng-Xue; Misra, Anil; Tamerler, Candan; Spencer, Paulette
Graphical abstract: Highlights: Dental adhesive capable of neutralization was achieved by incorporating lysine. Lysine promoted the degree of conversion of methacrylate and thermal stability of polymer. Lysine did not compromise the mechanical properties of polymer in dry and wet conditions. Abstract: Objectives: The objective of this study was to explore the effect of lysine integration to dental adhesives with respect to the polymerization kinetics, neutralization capacities in the acidic microenvironment, dynamic mechanical properties, and thermal properties. Materials and method: Lysine was incorporated into liquid resin formulations at 2.5 and 5.0 wt % with additional water/ethanol co-solvents. The co-monomer system contained 2-hydroxyethyl-methacrylate (HEMA) and Bisphenol A glycerolate dimethacrylate (BisGMA) with a mass ratio of 45/55. The kinetics of photopolymerization, neutralization capacities, lysine-leaching, dynamic mechanical properties and thermal properties of the control and experimental adhesives were analyzed. Results: The degree of conversion of the experimental adhesive was increased substantially at 2.5 wt% lysine as compared to the control. The experimental polymers provided acute neutralization of the acidic microenvironment. Approximately half of the lysine was released from the polymer network within one month. Under dry conditions and physiologic temperatures, the incorporation of lysine did not compromise the storage modulus. Comparison of the thermal properties suggests that the more compact structure of the control adhesive inhibits movement of the polymer chains resulting in increased Tg . Significance: Incorporating lysine in the adhesive formulations led to promising results regarding modulating pH, which may serve as one aspect of a multi-spectrum approach for enhancing the durability of composite restorations. The results provide insight and lay a foundation for incorporating amino acids or peptides into adhesive formulations for pH modulation or desired bioactivity at the interfacial margin between the composite and tooth.